1995
DOI: 10.1248/bpb.18.859
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among Secretagogues on Pepsinogen Secretion from Rat Gastric Chief Cells.

Abstract: We examined the interaction among secretagogues that stimulate pepsinogen secretion through different pathways in vivo and in vitro. In in vitro study, a combined administration of secretin and carbachol or cholecystokinin octapeptide (CCK-8) to the culture medium of chief cells potentiated pepsinogen secretion. Moreover, the response induced by carbachol or CCK-8 with forskolin was greater than that with secretin. We examined the interaction among receptor-related second mediators, and found that carbachol- o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The potency of secretin for altering TER in these gastric epithelial monolayers indicates activation at a specific secretin receptor. Indirect evidence supports the existence of functional secretin receptors on gastric chief and mucous cells, but not parietal cells (11,20,25,28). To date, only one secretin receptor has been cloned and characterized (34).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The potency of secretin for altering TER in these gastric epithelial monolayers indicates activation at a specific secretin receptor. Indirect evidence supports the existence of functional secretin receptors on gastric chief and mucous cells, but not parietal cells (11,20,25,28). To date, only one secretin receptor has been cloned and characterized (34).…”
Section: Discussionmentioning
confidence: 97%
“…Secretin has well-defined effects on chief cells, stimulating pepsinogen secretion by canine chief cells, rat gastric glands, and purified guinea pig chief cells in vitro (20,25,28). Because chief cells are the major component of canine gastric epithelial monolayer cultures (3) and secretin induces pepsinogen release from these cultures (25), secretin is a candidate to regulate other actions in these gastric cells.…”
mentioning
confidence: 99%
“…Pepsinogen is secreted in response to a meal but also occurs during the interdigestive state [2]. In vivo and in vitro studies on pepsinogen secretion have demonstrated that acetylcholine and cholinergic agents stimulate pepsinogen secretion and this response is inhibited by cholinergic antagonists [3,4], suggesting that muscarinic cholinergic receptors are directly and strongly associated with the stimulation of chief cells for pepsinogen secretion [1]. In addition, pepsinogen secretion appears to be regulated by several hormones.…”
Section: Introductionmentioning
confidence: 99%